PEDAGOGI INKLUSIF DALAM PERSPEKTIF HADIS: ANALISIS TEMATIK ATAS KONSEP RIFQ DAN ‘ADALAH - Febrina Dyah Putri; Muhammad Asgar Muzakki; Ulfah Zakiyah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
Hadith as a source of Islamic teachings after the Qur'an not only contains legal instructions and creed, but also contains profound educational values as reflected in the teaching methods of the Prophet PBUH. However, so far modern inclusive pedagogy has been built more through contemporary educational theory, while hadith has not been widely used as a basis for building the concept of inclusive pedagogy. This research aims to understand and analyze the concepts of rifq (gentleness) and 'is (justice) in hadith as an important basis for inclusive pedagogy in a prophetic perspective. Using a thematic analysis approach, this study collects and examines relevant hadiths, then understands them textually and contextually, and enriches interpretation through classical scholars. The results of the study show that rifq reflects an educational ethics based on compassion, patience, wisdom, and communication that respects the condition of students, while 'is affirming the importance of justice, proportionate treatment, and rejection of all forms of discrimination. These two principles show that the Sunnah of the Prophet not only serves as the main reference, but also presents an educational perspective based on the Prophet's example that is humanistic, inclusive, and just.